不曾离弃社会的作者 ：新华作家苗芒作品研究 = The one who stood by his society : a study of the works of Miao Mang as a Singapore Chinese writer - 陈诗珈 Tan, Shi Jia (2011)
本文通过不同的主题来分析苗芒的作品，从而看出其不同的关怀面。苗芒是土生土长的新加坡人，于1950年代至1970年代活跃新马文坛，发表了不少散文及诗歌作品。苗芒创作的主题多样化，但关怀范畴却不曾离开过社会低层,是一个关心社会、热爱国家的现实主义者。随着政局的变动，他的作品中也渐渐出现了反殖民和爱国的成分。据本文统计，苗芒出版的七部作品共有192篇散文和诗歌，其中关怀社会与国家的篇章就占了109，其余的则是苗芒个人的情感抒发，大多展现了苗芒积极的态度。苗芒与新加坡一同成长，经历了一个国家的发展旅程—— 由殖民地，到成为马来亚的一部分，到最后成为一个新兴国家。因为拥有切身的体会，苗芒由年少的“少年不识愁滋味”的情感抒发，笔锋一转成为了关怀社会群众和国家的爱国青年，写出了更多情感真切的作品。This dissertation is a study of using different topics to analyze Miao Mang’s works, bringing out the different aspects which he is concerned about. Miao Mang was born in Singapore, and actively participated in the Malayan literary world during the 1950s to the 1970s. His works varied from topic to topic, but never-changing, is his concern for the lower classes of the society. He is one who cares about his society, and the well-being of his country. In the midst of the changes in the political situation, works of anti-colonialism and patriotism slowly emerged. According to the numbers collated in this dissertation, he published seven books, which consisted of 192 prose and poems, of which 109 of them showed his concern for the society and the country, and the rest his emotional expressions. Miao Mang grew up with Singapore, witnessing the progress of a country, from a colony to being part of Malaya, and becoming a developing country. Having experienced such direct impact, there was a change in his style of writing, from an adolescent who laments over trivial emotions to a youth who is concern about his society and his country, therefore producing more works with real emotions.